The deep underground Bellotti Ion Beam Facility—status and perspectives - Junker, Matthias; Imbriani, Gianluca; Best, Andreas; Boeltzig, Axel; Compagnucci, Alessandro; Di Leva, Antonino; Ferraro, Federico; Rapagnani, David; Rigato, Valentino (Frontiers in Physics, 2023)
For more than three decades, accelerators are in use in the underground laboratories of the Laboratori Nazionali del Gran Sasso (LNGS), located in central Italy. The LUNA Collaboration has exploited the potential of the site's low cosmic ray background to achieve important and often groundbreaking results in the field of nuclear astrophysics. This long success story stimulated the installation of accelerators in deep underground laboratories also in other countries, including the USA and China.Recently, LNGS took a major step forward with the activation of the Bellotti Ion Beam Facility, which will provide ion beams to the scientific community for research not only in nuclear astrophysics, but in all fields that can benefit from the low cosmic ray background conditions of the underground site.